Reversible click chemistry at the service of macromolecular materials. Part 4: Diels-Alder non-linear polycondensations involving polyfunctional furan and maleimide monomers - Gandini, Alessandro
The polymerisation of furan monomers and the exploitation of some of the chemical peculiarities of the furan heterocycle have generated a wide diversity of macromolecular materials based on renewable resources. In particular, the application of the DA cycloaddition to the macromolecular chemistry opened new ways to synthesize materials with unique properties, such as self-mendability and network recyclability. In this study, non-linear polycondensations between di- and tri-functional furan (A(n)) and maleimide (B-m) monomers by means of the DA reaction are presented. The use of complementary monomers bearing more than two functionalities led to highly crosslinked structures under appropriate stoichiometric conditions, and thus, can be applied in the preparation of \"mendable\" materials.